Development of Teaching Materials Based on Differentiated Learning to Improve Critical Thinking Dimensions of The Pancasila Learner Profile - Farhania Maulida; Andhin Dyas Fitriani; Mela Darmayanti (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to develop teaching materials based on differentiated learning to improve critical thinking dimensions of the Pancasila Learner Profile for students in elementary schools. This research uses the Design and Development (D&D) method using the ADDIE model, which consists of five stages, i.e., analysis, design, development, implementation, and evaluation. The research participants comprised grade 3 elementary school students, material experts, media experts, and learning experts. The data collection techniques used in this study were filling out work logs, testing expert validation, and learner assessments. The analysis used in this research is qualitative and quantitative data analysis. The results of this study are teaching materials in three series, namely visual series, audio series, and kinesthetic series. The study results were teaching materials obtained a validation assessment with an outstanding category. Then, to test the effectiveness of N-Gain, the results showed effectiveness in the moderate category. Thus, Teachers can utilize this differentiated teaching material to teach the material and develop students' critical thinking skills in learning IPAS in elementary school.